Courting gender bias: an examination of women’s experiences in the profession of law in Kansas - Lueker, Suzanne J. (Kansas State University, 2012)
This study examines the issue of gender bias and other gendering processes within the profession of law in Kansas. Although women have made great strides toward equality within the law profession, there are still glaring disparities between men’s and women’s occupational attainment. Women enter law school at similar rates as men do; however, they are not similarly represented in the legal profession upon graduation, or throughout their careers. Utilizing a theory of gendered organizations, this study seeks to investigate what impact, if any, certain sociodemographic factors, sector of law, mentorship, and perceptions of discrimination, have on women’s levels of job satisfaction. To accomplish this goal, this study makes connections between previous research conducted by the Kansas Bar Association, and more recent survey data modeled after the original KBA research. Underlying structures and ingrained interactions are examined quantitatively, to gain a better understanding of the gendered processes that women experience within the profession of law in Kansas.
Keywords: Gender bias; Gender and law; Gender and job satisfaction in law; Gender bias and law; Kansas Bar Association and gender bias; Women attorneys and judges and gender bias; Sociology (0626)